2010
DOI: 10.1186/ar2918
|View full text |Cite
|
Sign up to set email alerts
|

Mitochondrial dysfunction and mitophagy activation in blood mononuclear cells of fibromyalgia patients: implications in the pathogenesis of the disease

Abstract: IntroductionFibromyalgia is a chronic pain syndrome with unknown etiology. Recent studies have shown some evidence demonstrating that oxidative stress may have a role in the pathophysiology of fibromyalgia. However, it is still not clear whether oxidative stress is the cause or the effect of the abnormalities documented in fibromyalgia. Furthermore, the role of mitochondria in the redox imbalance reported in fibromyalgia also is controversial. We undertook this study to investigate the role of mitochondrial dy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

9
122
0
13

Year Published

2012
2012
2021
2021

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 136 publications
(144 citation statements)
references
References 43 publications
9
122
0
13
Order By: Relevance
“…In this sense, enhancing basal muscle tone (e.g., through multicomponent exercise programs) could potentially improve resting-state functional connectivity in sensory-motor systems and reduce peripheral sensitization and clinical pain, which warrants further research. Similarly, peripheral mechanisms (e.g., abnormalities in microcirculatory capillaries [35] or irregularities in mitochondria [36]) might reduce peripheral tissue oxygenation and lead to central sensitization in FM patients. Thus, increasing tissue oxygenation as a result of aerobic exercise could potentially diminish peripheral and central sensitization and reduce clinical pain (3).…”
Section: Discussionmentioning
confidence: 99%
“…In this sense, enhancing basal muscle tone (e.g., through multicomponent exercise programs) could potentially improve resting-state functional connectivity in sensory-motor systems and reduce peripheral sensitization and clinical pain, which warrants further research. Similarly, peripheral mechanisms (e.g., abnormalities in microcirculatory capillaries [35] or irregularities in mitochondria [36]) might reduce peripheral tissue oxygenation and lead to central sensitization in FM patients. Thus, increasing tissue oxygenation as a result of aerobic exercise could potentially diminish peripheral and central sensitization and reduce clinical pain (3).…”
Section: Discussionmentioning
confidence: 99%
“…Ten nuclear genes involved in CoQ biosynthesis have been identified in humans and disease-causing mutations, which lead to primary CoQ deficiency, have been identified in some of these genes [25]. Secondary CoQ deficiency has been identified in a wide range of diseases, including mitochondrial diseases, neurodegenerative diseases, such as Parkinson's disease, cancer, fibromyalgia, and in patients undergoing statin treatment [22,26,27]. Currently, primary and secondary CoQ deficiencies are the focus of some attention, due to the high prevalence of the latter, and the potential for treatment.…”
Section: Discussionmentioning
confidence: 99%
“…This is clinically important since mitochondrial dysfunction can initiate a series of cellular events that promote pro-inflammatory signaling pathways or lead to cell death. Several studies have characterized mitochondrial function of peripheral blood mononuclear cells and platelets in conditions such as fibromyalgia, diabetes, septic shock, and Alzheimer's disease [3][4][5][6][7] . For example, a recent study evaluated the bioenergetics of platelets as a marker for mitochondrial function and found that platelets from Type 2 diabetic patients had diminished mitochondrial oxygen consumption 7,8 .…”
Section: Introductionmentioning
confidence: 99%